2018
DOI: 10.1002/chem.201803178
|View full text |Cite
|
Sign up to set email alerts
|

Metallacarboranes on the Road to Anticancer Therapies: Cellular Uptake, DNA Interaction, and Biological Evaluation of Cobaltabisdicarbollide [COSAN]

Abstract: After uptake by U87 MG and A375 cancer cells, cobaltabisdicarbollide [COSAN] distributes between membrane and nucleus and presents no relevant cytotoxicity against both cell lines even for long incubation times. The cytotoxicity of Na[COSAN] was also tested towards one normal cell line, the V79 fibroblasts, in order to ascertain the noncytotoxic profile of the compound. As the cell's nucleus contains DNA, the interaction between [COSAN] and double-stranded calf thymus DNA (CT-dsDNA) has been investigated. Ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
120
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 91 publications
(138 citation statements)
references
References 68 publications
8
120
0
1
Order By: Relevance
“…[1][2][3][4][5] Among the various derivatives of carboranes, special attention is paid to p-complexes of transition metals with carborane ligands, called metallacarboranes. The most known of them, cobalt bis(dicarbollide) [3,3 0 -Co(1,2-C 2 B 9 H 11 ) 2 ] À attracts increasing interest from researchers working in various elds from medical chemistry to [6][7][8][9][10][11] materials science [12][13][14][15][16][17][18] to due to its extraordinary high stability, low toxicity 19 and almost unlimited possibilities for chemical modication. 20,21 Recently, we suggested that cobalt bis(dicarbollide) can be used as a structural element in the design of molecular switches.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Among the various derivatives of carboranes, special attention is paid to p-complexes of transition metals with carborane ligands, called metallacarboranes. The most known of them, cobalt bis(dicarbollide) [3,3 0 -Co(1,2-C 2 B 9 H 11 ) 2 ] À attracts increasing interest from researchers working in various elds from medical chemistry to [6][7][8][9][10][11] materials science [12][13][14][15][16][17][18] to due to its extraordinary high stability, low toxicity 19 and almost unlimited possibilities for chemical modication. 20,21 Recently, we suggested that cobalt bis(dicarbollide) can be used as a structural element in the design of molecular switches.…”
Section: Introductionmentioning
confidence: 99%
“…E: carboranyl nucleosides [42]. F: boron-containing nanoparticles [44] compounds indicated above, third-generation agents including one or more polyhedral anions of borane or carboranes have been investigated [30]. The stable boron delivery agents with low and high molecular weight connected with a tumor-targeting component or moiety via a hydrolytically stable linkage (boron carriers) belong to this group of compounds ( Figure 2).…”
Section: Third-generation Boron Compoundsmentioning
confidence: 99%
“…The stable boron delivery agents with low and high molecular weight connected with a tumor-targeting component or moiety via a hydrolytically stable linkage (boron carriers) belong to this group of compounds ( Figure 2). In particular, these thirdgeneration boron compounds include boronated DNA intercalators [30], boronated amino acids [31], boronated lipopeptides [32], boronated peptides [33], boronated folate receptor [34], boronated epidermal growth factor (EGF) or epidermal growth factor receptor (EGFR) monoclonal antibodies (MAbs) [35], boron-containing immunoliposomes [36] and liposomes [37,38], BSH-loaded polymeric micelles [39], transferrin-polyethylene glycol liposomes [40], maleimide-functionalized closo-dodecaborate albumin conjugates [41], carboranyl nucleosides [42], boronated porphyrins [43], boron-containing nanoparticles [44] coupled with cationic microbubble-assisted focused ultrasound (MB+FUS) treatment [45], pentanuclear porphyrazine complexes [46], boronated cyclic peptides [47], and boron nitride nanotubes [48].…”
Section: Third-generation Boron Compoundsmentioning
confidence: 99%
“…20,21 Besides, substituents can also be introduced with good control to at least a certain number of boron vertices, making the research in this area very versatile and attractive for BNCT. The icosahedral closo-C 2 B 10 H 12 carborane 22 and metallacarborane 23 [M(C 2 B 9 H 11 ) 2 ] À clusters are 3D aromatic moieties, possessing high symmetry and stability, 24 and generally low cytotoxicity, 25,26 being good candidates for BNCT. 25,[27][28][29] In this frame, several compositions for potential BNCT applications have been developed, [30][31][32][33][34][35] including high boron-loaded DNA-oligomers, 36 periphery-decorated and core-initiated borane polyanionic macromolecules, 37 peptide-cobalt bis(dicarbollide) conjugates, 38 nucleoside-boron cluster conjugates 39,40 and cholesterol-metallacarborane conjugates, 41 among others.…”
Section: Introductionmentioning
confidence: 99%